Similar Anatomical Reduction and Lower Complication Rates With the Sinus Tarsi Approach Compared With the Extended Lateral Approach in Displaced Intra-Articular Calcaneal Fractures. Issue 6 (June 2017) - Schepers, Tim; Backes, Manouk; Dingemans, Siem A.; de Jong, Vincent M.; Luitse, Jan S. K.
Abstract : Objectives: To investigate whether the sinus tarsi approach (STA) allows for a similar anatomical reduction of the posterior talocalcaneal facet as the extended lateral approach (ELA) and compare the rate of postoperative wound complications. Design: Retrospective. Setting: Level 1 trauma center. Patients: All consecutive patients from 2012 to 2015 with a closed displaced intra-articular calcaneal fracture Sanders type II and III surgically treated with the ELA (N = 60) and the STA (N = 65). Main Outcome Measurements: Wound complications, timing of surgery, operative time, length of postoperative hospitalization, and reduction of the posterior facet and calcaneal body. Results: Incidence of wound complications, time to surgery, postoperative duration of hospital admission, and number of hospital admissions because of wound complications were significantly different between the ELA group and STA group. There was no significant difference in restoration of calcaneal anatomy with either approach. Importantly, the STA was performed in a median duration of 105 minutes and the ELA in a median of 134 minutes, accounting for nearly half an hour difference in operating time ( P < 0.001). Conclusions: The largest benefit of the STA was found in the significant reduction in wound complications and operative time, where time to closure may have accounted for the latter difference. This difference was without a compromise in reduction. Additional studies comparing functional outcome, especially rates of subtalar arthrosis, will be needed to determine the long-term benefits of STA. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.